2018
DOI: 10.1080/1828051x.2018.1496040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic supplementation on milk production, blood metabolite profile and enzyme activities of ewes during lactation

Abstract: There is scarce information regarding the effects of probiotics in the diet of lactating ewes on milk yield and composition as well as on metabolite concentrations and enzyme activities in blood. Sixteen Sanjabi ewes, kept under the same feeding and management practices, were divided in two equal groups. The ewes in the first group were fed a diet without probiotics, while the ewes of the second group were fed the same diet supplemented with two grams of commercial probiotics (PrimaLac V R 454 Feed grade, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Hassan et al (2019) reported that the use of Ruminococcus flavefaciens in Baki lambs affected final BW and daily BWG. However, Kafilzadeh et al (2019) stated that probiotic supplementation did not affect BW of sheep at the end of their study. Probiotic supplementation in powder or liquid form increased in vitro DM digestibility, nutrient digestibility and daily BWG for lambs (Hassan et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hassan et al (2019) reported that the use of Ruminococcus flavefaciens in Baki lambs affected final BW and daily BWG. However, Kafilzadeh et al (2019) stated that probiotic supplementation did not affect BW of sheep at the end of their study. Probiotic supplementation in powder or liquid form increased in vitro DM digestibility, nutrient digestibility and daily BWG for lambs (Hassan et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Peng et al (2018) reported that the probiotic additive did not affect MDA and total antioxidant capacity values, but increased the SOD and GSH-Px values. Kafilzadeh et al (2019) found that probiotic supplementation rarely affected the blood plasma metabolite content and enzyme activities of sheep. L. fermentum showed significant in vitro antioxidant capacity, which increased its total antioxidant potential (Persichetti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…There is limited information on the effect of inulin on feed intake in ewes, but DM intake often depends on the fiber digestion rate. It has been reported that feed additives with the ability to modulate rumen microorganisms and increase the efficiency of microbial protein synthesis lead to higher activity of fibrinolytic enzymes and thereby increase the rate of fiber digestion (Kafilzadeh et al ., 2019). Increasing fiber digestibility can decrease the effects of rumen filling, which can ultimately lead to increased feed intake, but we did not observe this.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, due to the need to limit the use of antibiotics, increasing interest has been addressed to the use of yeasts and their products in animal nutrition, in particular in pet-food industry, which produce a wide range of diets and supplements containing yeast, as well as yeast cell walls, both for dogs and cats. Different species of Saccharomyces, in particular S. cerevisiae, are largely adopted as prebiotics in animal nutrition (Desnoyers et al 2009;Mackenthun et al 2013), as well as supplements (Liu et al 2008;Kafilzadeh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%